Presentation attack detection for face recognition using remote photoplethysmography and cascaded fusion - EROĞLU ERDEM, ÇİĞDEM (TUBITAK SCIENTIFIC & TECHNICAL RESEARCH COUNCIL TURKEY, 2021)
Spoofing (presentation) attacks are important threats for face recognition and authentication systems, which try to deceive them by presenting an image or video of a different subject, or by using a 3D mask. Remote (non-contact) photoplethysmography (rPPG) is useful for liveness detection using a facial video by estimating the heart-rate of the subject. In this paper, we first compare the presentation attack detection performance of three different rPPG-based heart rate estimation methods on four datasets (3DMAD, Replay-Attack, Replay-Mobile, and MSU-MFSD). We also present a cascaded fusion system, which utilizes a multistage ensemble of classifiers using rPPG, motion-based (including head-pose, eye-gaze and eye-blink), and texture-based features. Experimental results show that the proposed method outperforms several other presentation attack detection methods in the literature, which utilize rPPG.
Keywords: Face recognition; presentation attack detection; non-contact photoplethysmography; rPPG